DETERMINAN NILAI PERUSAHAAN MANUFAKTUR - Ericha Citra Agustina; muhammad Aufa (PROCEEDING UMSURABAYA, 2022)
This study was conducted to determine the effect of dividend policy, debt policy, profitability and company size on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Firm value in this study was measured using Price to Book Value (PBV). The data collection method used purposive sampling. The number of samples used was 52 companies. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that dividend policy has no effect on firm value. Debt policy has a negative effect on firm value. Then profitability and firm size have a significant positive effect on firm valueKeywords:Company Value; Dividend Policy; Debt Policy; Profitability and Company SizeÂ